Therapeutic Mechanisms of Stem Cell–Derived Exosomes for Neurological Disorders: An Overview - Congying Lin; Lixin Qi; Xiuying Gao; Lei Hu; Bo Qian; Yixuan Deng; Chunting Zhou; Chenyi Wang; Guanhao Liu; Qiang Ding; Zhenlang Lin; Xuwei Zhu; et al. (Molecular Neurobiology, 2026)

Application of nanomaterials in central nervous system disorders - Yixuan Deng; Yani Feng; Bangming Ye; Lei Hu; Lixin Qi; Chenyi Wang; Chunting Zhou; Guanhao Liu; Xiuying Gao; Congying Lin; Qiang Ding; Ziming Zhao; et al. (Psychopharmacology, 2025)

A biomimetic liposome platform targeting non-small cell lung cancer to modulate the inflammatory and metabolic microenvironment for enhanced therapy - Xinyu Jiang; Pengfei Mao; Minghui Wang; Dingchao Shen; Linyi Zhang; Yingyi Zhao; Xindan Liang; Zihao Huang; Yunzhi Wang; Yinhao Lin; Zihao Tao; Yuqi Han; et al. (Chemical Engineering Journal, 2025)

Synergetic carbon emission reduction in the construction industry: A spatial correlation perspective from urban agglomerations in southeast coastal China - Xiaojuan Li; Gaona Duan; Chengxin Lin; Yun Lin; Jieyi Chen; Congying Fang; Tinghui Zhang (Energy and Buildings, 2025)

The involvement of auxin response factor OsARF7 in positively regulating root development by mediating the expression of OsCRL1 in rice (Oryza sativa L.) - Congying Sun; Kai Fan; Xin Wang; Honghai Liu; Nuoping Guo; Wanyu Liu; Guixiang Ye; Weiwei Lin; Wenxiong Lin; Zhaowei Li (Plant Molecular Biology, 2025)

Effects of loading paths and initial densities on mechanical response and gradation evolution of calcareous sand - Jiarui Chen; Yaolan Tang; Jianhong Ye; Chunshun Zhang; Zhenghong Lin; Congying Li; Wei Wei; Jie Dong (Engineering Geology, 2025)

YY1 as a mediator to enhance the resistance of KRAS mutant colorectal cancer cells to cetuximab - Yi Ma; Yuli Hu; Yi Lin; Congying Wang; Yujie Lv; Wei Chen (Journal of Genetics, 2024)

A coupled hand and surface hygiene criterion on heterogeneous surface touch networks - Shenglan Xiao; Congying Li; Fangli Zhao; Ruizhen Lin; Nan Zhang; Yuguo Li (Journal of Hazardous Materials, 2024)

Density functional theory of the effect of different directional strains on the physical properties of coal - PengXiang Zhao; ChengYue Wang; ShuGang Li; ShaoRong Li; HaiFei Lin; CongYing Cao; MingChao Yong; LaoLao Wang (Fuel, 2024)

Effects of exercise on muscle fiber conversion, muscle development and meat quality of Sunit sheep - Lin Su; Congying Zhao; Bing Sun; Lu Dou; Chenlei Wang; Zhihao Yang; Tianle Li; Ye Jin (Meat Science, 2024)

Straw management adopted by large farms sustains grain yield but mitigates greenhouse gas emissions - Zhenzhen Li; Yong Lin; Zheng-Rong Kan; Sana ur Rehman; Atta Mohi Ud Din; Feng-Min Li; Shixiang Zhang; Ping Wu; Yingfu Ding; Chensheng Xu; Congying Rao; Huaxin Dai; et al. (Field Crops Research, 2024)

Impact of urban land development on carbon emission performance based on a multidimensional framework - Xinhui Feng; Xinle Lin; Yan Li; Jiayu Yang; Er Yu; Congying He; Kaige Lei; Weiming Gao (Environmental Impact Assessment Review, 2024)

Physiological response of red macroalgae Pyropia yezoensis (Bangiales, Rhodophyta) to light quality: a short-term adaptation - Xuefeng Zhong; Shuai Che; Congying Xie; Lan Wu; Xinyu Zhang; Lin Tian; Chan Liu; Hongbo Li; Guoying Du (Algae, 2023)
Light quality is a common environmental factor which influences the metabolism of biochemical substances in algae and leads to the response of algal growth and development. Pyropia yezoensis is a kind of economic macroalgae that naturally grows in the intertidal zone where the light environment changes dramatically. In the present study, P. yezoensis thalli were treated under white light (control) and monochromatic lights with primary colors (blue, green, and red) for 14 days to explore their physiological response to light quality. During the first 3 days of treatment, P. yezoensis grew faster under blue light than other light qualities. In the next 11 days, it showed better adaptation to green light, with higher growth rate and photosynthetic capacity (reflected by a higher rETRmax = 61.58 and Ek = 237.78). A higher non-photochemical quenching was observed in the treatment of red light than others for 14 days. Furthermore, the response of P. yezoensis to light quality also results in the difference of photosynthetic pigment contents. The monochromatic light could reduce the synthesis of all pigments, but the reduction degree was different, which may relate to the spectral absorption characteristics of pigments. It was speculated that P. yezoensis adapted to a specific or changing light environments by regulating the synthesis of pigments to achieve the best use of light energy in photosynthesis and premium growth and metabolism.

A GWA study reveals genetic loci for body conformation traits in Chinese Laiwu pigs and its implications for human BMI - Lisheng Zhou; Jiuxiu Ji; Song Peng; Zhen Zhang; Shaoming Fang; Lin Li; Yaling Zhu; Lusheng Huang; Congying Chen; Junwu Ma (Mammalian Genome, 2016)